Graduated Controlled Atmosphere: A Novel Approach to Increase “Duke” Blueberry Storage Life - Falagán, Natalia; Miclo, Tiana; Terry, Leon A. (Frontiers in Plant Science, 2020)
Blueberries (Vaccinium corymbosum L.) are highly valued for their health-promoting potential yet, they are extremely perishable. Controlled atmosphere (CA) strategies reduce blueberry respiratory metabolism, slowing down senescence. However, the sudden change of atmosphere could elicit a physical abiotic stress in the fruit, negatively affecting quality. We propose an innovative approach based on controlled graduation to slowly reach optimum gas storage conditions as an alternative to standard CA. For two consecutive seasons, “Duke” blueberries were subjected to four different storage conditions: control (air); standard CA (sudden exposure to 5 kPa O2 and 10 kPa CO2 across the experiment); GCA3 and GCA7 (gradually reaching 5 kPa O2 and 10 kPa CO2 in 3 and 7 days respectively). Fruit were stored for 28 days at 0 ± 0.5 ºC. Real-time respirometry provided an in-depth insight of the respiratory response of blueberries to their gas environment. Blueberries subjected to GCA treatments had a lower steady-state respiration rate compared to control and CA fruit. This indicated a reduction in metabolic activity that positively impacted quality and storage life extension. For example, GCA3 and GCA7 blueberries had a 25% longer storage life when compared to control, based on reduced decay incidence. In addition, GCA fruit were 27% firmer than control and CA fruit after 28 d of cold storage. GCA3 had a positive effect on maintaining individual sugars concentrations throughout the experiment, and both GCA treatments maintained ascorbic acid content close to initial values compared to a decrease of 44% in the control fruit at the end of the experiment. This work provides a paradigm shift in how CA could be applied and a better understanding of blueberry physiology and postharvest behaviour.